Four Cities : a Study in Comparative Policy Making - Williams, Oliver P. (University of Pennsylvania Press, 2016)
This is an analysis of the political process in four middle-sized unnamed American cities between the years 1948 and 1957.
Keywords: Municipal government -- United States -- Case studies.; Administration municipale -- États-Unis -- Études de cas.; POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development.; Municipal government; United States; Case studies